Pathological investigation of infectious diseases in free- ranging black-tufted marmosets (Callitrix penicillata) and implications for public health and conservation in Brazil - Wilson, Tais Meziara (2021)
Tese (doutorado) — Universidade de Brasília, Faculdade de Agronomia e Medicina Veterinária, 2021.